MOTIVASI GURU DALAM MELAKSANAKAN TUGAS DAN FUNGSI PELAYANAN KEPADA SISWA DI SMA NEGERI 3 TAPUNG KABUPATEN KAMPAR - Hikmatul Wafiroh; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study is to examine and analyze the motivation of teachers in performing tasks and service functions to students in SMA Negeri 3 Tapung Kampar regency based on intrinsic factors and extrinsic factors. This research method uses a combination approach between quantitative and qualitative used to process the data obtained from the research location. Data collection techniques in this study using questionnaire method and study data in the form of reports and evidence relating to research. The data were analyzed quantitatively by using frequency tables and the end result was determined by the mean value. The results showed that the average score of teacher motivation of intrinsic factor is 4.13 with very good category. The highest score indicator is the responsibility with the average score reached 4.32 with very good category. While the average score of extrinsic factor is 4.10 with very good category. Indicator that get highest score is interpersonal relationship with average score reached is 4,42 with very good category. So it can be concluded that most teachers in SMA Negeri 3 Tapung have been motivated to work in carrying out the duties and functions of excellent service, both from intrinsic factors and from extrinsic factors resulting in excellent performance. As for the input is the motivation of teacher work must be maintained and improved again in order to achieve quality education in SMA Negeri 3 Tapung.Keywords: Teacher Motivation, Service Function